Impact of mild traumatic brain injury on health behaviors - Yookyung Lee; Yoonjeong Choi; Jooeun Jeon; Ja-Ho Leigh; Don-Kyu Kim; Byung-Mo Oh (Scientific Reports)
Abstract Health-related behavioral changes may occur following traumatic brain injury. We focused on understanding the impact of mild traumatic brain injury (TBI) on health-related behaviors and identifying factors associated with such changes. We utilized health check-up records from the Korean National Health Insurance Service database spanning January 1, 2009, to December 31, 2017. The sample included 49,212 patients diagnosed with mild TBI and 1:1 matched controls who participated in national health check-ups in 2009–2010, 2011–2012, and 2016–2017. Multivariable logistic regression analysis was utilized to examine the association between mild TBI and short- and long-term health-related behavioral changes. Mild TBI was significantly associated with an increased risk of insufficient physical activity at the short- [odds ratio (OR), 1.04; 95% confidence interval (CI), 1.01 − 1.07] and long-term (OR, 1.06; 95% CI, 1.03 − 1.09) follow-ups. Age ≥ 65 years and female sex were significant effect modifiers for insufficient physical activity (OR, 1.11; 95% CI, 1.02 − 1.21) and smoking (OR, 1.31; 95% CI, 1.14 − 1.51), respectively. Mild TBI may lead to detrimental health-related behavioral changes, varying by age and sex. Thus, age- and sex-specific interventions may be needed to address these changes.